Effects of fatigue on the leg kinetics in all-out 600m running - Kadono, H.; Ae, M.; Suzuki, Y.; Shibayama, K. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to study effects of fatigue on ground reaction forces (GRF) and leg kinematics in all-out 600m running (simulating a positive pacing strategy of the 800m race). Eight male middle-distance runners were asked to perform an all-out 600m run and a non-fatigued 80m run with the same velocity as at the 550m mark of the all-out 600m run. Runs were videotaped (300Hz) in 2D and the ground reaction forces were measured (500Hz) at the 150m and 550m marks of the 600m run and the 50m mark of the 80m run. Step length, GRF, ankle plantar flexion torque and knee extension torque of the support leg decreased due to fatigue. Results suggest that in the final stage of a 800m race, the runner should not try to increase step length by applying great force to the ground, but should shorten the aerial phase and step time by faster recovery phase.